Integrating microsurgical reconstruction in head and neck oncology: a collaborative learning curve experience - Oprescu, Anca Emilia (Medicine and Pharmacy Reports, 2026)
Background. Microsurgical head and neck reconstruction requires specialized expertise that can be challenging to develop in regional healthcare settings. This study documents the collaborative learning curve experience of establishing microsurgical capabilities through multidisciplinary team integration. Methods. A retrospective case series analyzed 8 consecutive head and neck microsurgical reconstructions performed between October 2018 and October 2021 in Constanta, Romania. All procedures were performed by the same primary surgeon with systematic collaborative multidisciplinary support. Data included patient demographics, risk factors, collaborative team composition, operative metrics, outcomes, and learning curve progression assessment. Results. Eight patients (5 male, 3 female) underwent reconstruction for squamous cell carcinoma (SCC, 50%), basal cell carcinoma (BCC, 25%), radiodermitis (12.5%), and iatrogenic facial palsy (12.5%). Procedures included mandibular reconstruction (37.5%), tongue/floor of mouth reconstruction (25%), facial reanimation (12.5%), nasal reconstruction (12.5%), and orbital coverage (12.5%). All cases utilized multidisciplinary teams averaging 3.4 members, with maxillofacial surgeons participating in 75% and general surgeons in 100% of cases. During the early learning phase, operative time decreased from 15 to 10 hours and surgeon confidence advancement from “Low” to “Medium-High” levels. Overall success rate was 62.5% with one partial success (12.5%) and two failures (25%). Risk factors were present in 75% of cases, with failures associated with cumulative risk factors and immunocompromised status. Conclusions. Microsurgical head and neck reconstruction can be successfully integrated into regional healthcare systems through systematic collaborative learning approaches. The multidisciplinary model enabled safe skill acquisition while maintaining acceptable outcomes during the early learning phase. Key insights include avoiding cumulative risk factors during initial learning and ensuring comprehensive preoperative optimization. This collaborative framework describes an early institutional experience that may be informative for other centers initiating microsurgical programs.